Understanding environmental decision-making in forest restoration: the role of latent attitudes, attribute non-attendance, and choice behavior - Jeon, Chulhyun (Frontiers in behavioral economics, 2025)
IntroductionAs forests face growing threats from fires, pests, and disease, understanding public preferences for restoration policies has become increasingly urgent. This study addresses the need for more behaviorally realistic approaches in environmental valuation.MethodsA discrete choice experiment was conducted in Korea to explore how individuals make environmental decisions. The study incorporates latent environmental attitudes, attribute non-attendance (ANA), and heterogeneous choice behavior using advanced econometric models, including the independent availability logit and latent class analysis.ResultsFindings reveal that respondents do not ignore entire attributes but selectively disregard specific attribute levels. Distinct behavioral classes were identified, ranging from deterministic to probabilistic decision types. Latent attitudes significantly influenced willingness to pay (WTP), with some groups showing reluctance to pay due to self-benefit orientation.DiscussionThese results highlight the importance of recognizing behavioral subgroups when designing restoration policies. Integrating behavioral insights into valuation enhances the relevance and acceptability of forest restoration programs. This research provides practical guidance for developing targeted, socially accepted environmental policies.